Pengaruh Filsafat Yunani Terhadap Pemikiran Islam - Wahda, Nur Aqiqah; Santalia, Indo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to examine the influence of Greek philosophy on Islamic thought, focusing on how this classical thinking shaped intellectual development within the Islamic tradition. Greek philosophy, particularly the works of philosophers such as Socrates, Plato, and Aristotle, has made significant contributions to the development of theological thought, science, and culture in Islam. The research employs a literature review method with a qualitative approach, where relevant data is collected from literature, articles, and related documents. Through the analysis of historical texts and intercultural dialogues, this study reveals how the acceptance and adaptation of Greek thought by Muslim scholars have resulted in an intellectual synergy that enriches the Islamic tradition. The findings indicate that the influence of Greek philosophy extends beyond the philosophical realm, having broad implications for the formation of mindsets and cultural development within the context of Islam.